Use pattern of pesticides and their predicted mobility into shallow groundwater and surface water bodies of paddy lands in Mahaweli river basin in Sri Lanka. Issue 1 (2nd January 2017) - Aravinna, Piyal; Priyantha, Namal; Pitawala, Amarasooriya; Yatigammana, Sudharma K.
ABSTRACT: Pesticides applied on agricultural lands reach groundwater by leaching, and move to offsite water bodies by direct runoff, erosion and spray drift. Therefore, an assessment of the mobility of pesticides in water resources is important to safeguard such resources. Mobility of pesticides on agricultural lands of Mahaweli river basin in Sri Lanka has not been reported to date. In this context, the mobility potential of 32 pesticides on surface water and groundwater was assessed by widely used pesticide risk indicators, such as Attenuation Factor ( AF ) index and the Pesticide Impact Rating Index (PIRI) with some modifications. Four surface water bodies having greater than 20% land use of the catchment under agriculture, and shallow groundwater table at 3.0 m depth were selected for the risk assessment. According to AF, carbofuran, quinclorac and thiamethoxam are three most leachable pesticides having AF values 1.44 × 10 −2, 1.87 × 10 −3 and 5.70 × 10 −4, respectively. Using PIRI, offsite movement of pesticides by direct runoff was found to be greater than with the erosion of soil particles for the study area. Carbofuran and quinclorac are most mobile pesticides by direct runoff with runoff fractions of 0.01 and 0.08, respectively, at the studied area. Thiamethoxam and novaluron are the most mobile pesticides by erosion with erosion factions of 1.02 × 10 −4 and 1.05 × 10 −4, respectively. Expected pesticide residue levels in both surface and groundwater were predicted to remain below the USEPA health advisory levels, except for carbofuran, indicating that pesticide pollution is unlikely to exceed the available health guidelines in the Mahaweli river basin in Sri Lanka.